HEALTH PROMOTING BREAD; COMPRISING NATURAL-MIRACLE ANTHOCYANINS - Refiker, Hurmus; Asir, Suleyman (Journal of microbiology, biotechnology and food sciences, 2021)
The phenolic aqueous extract from red cabbage was incorporated into bread and stability and contribution of anthocyanins comprising bread samples have been investigated. Assessment of total monomeric anthocyanin in sample bread stored both at room temperature and at 4 oC, on different days; first, third, sixth and 32nd day of storage, was carried out. The total phenolic content and total antioxidant capacity of sample bread were measured by the Folin-Ciocalteu (FC) procedure and the oxygen radical absorbance capacity (ORAC) method, respectively. Total phenolic contents were estimated as 91.88 Â± 2.42 mg GAE/100 g and ORAC value was calculates as 1387 Â± 153 mmol TE/100 g (DW;Dry weight). No colonies of mold were monitored in sample bread when kept at 4 oC for almost three weeks retaining its antioxidant properties. These innovative and health promoting bread samples might be inspiring for public and the molecular gastronomy and food science researches as well as in the near future.